(untitled) (FUDMA JOURNAL OF SCIENCES, 2025)
Land-use planning is the systematic assessment of land and water potential, alternatives for land-use, and economic and social conditions in order to select and adapt the best land-use options. The aim of this study is to examine how geospatial information is the bedrock for land use planning and management with a focus on estate housing development. The project site is located at Eleko, Lagos State, Nigeria. The three (3) survey controls used for the connection of the project are ZTT 37/17, ZTT 37/18 and ZTT 37/19. Digital Survey instruments (Leica TCR 307, Level) were used for the acquisition of geospatial data of the site. Tacheometric survey method for spot heighting and ray method for detailing of features within and around the site. Grid levelling was carried out at 10 m intervals with staking at 10 m. The results obtained show that the total perimeter of the traverse is 839.805 m; total area of the site is 3.132 Hectares; and the linear accuracy of the traverse is 1/15,000. Grid levelling was carried out at 10 m intervals with staking at 10 m. This provides the elevation for each point which was used to provide contours for the terrain; and finally the production of topographic map and Digital Terrain Model (DTM) of the site which are used as tools for land use planning and its management. Therefore, it can be concluded that geospatial information such as topographic map and DTM are the bedrock for land use planning and management.